2011
DOI: 10.1111/j.1525-1446.2011.00956.x
|View full text |Cite
|
Sign up to set email alerts
|

Benefits, Barriers, Sources of Influence, and Prostate Cancer Screening Among Rural Men

Abstract: In this primarily African American sample, significant barriers to PCS among rural men were indentifed. PC health education may need to include family, whom study participants highly reported as a source of influence regarding their PCS decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 13 publications
4
18
0
Order By: Relevance
“…Participants in the study mentioned a lack of knowledge of where to go and how to do screening tests, a lack of emphasis on the screening tests, and a fear of thinking about the disease as the most common barriers to the prostate cancer screening. These results are consistent with the results of some previous studies (11,13,41).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Participants in the study mentioned a lack of knowledge of where to go and how to do screening tests, a lack of emphasis on the screening tests, and a fear of thinking about the disease as the most common barriers to the prostate cancer screening. These results are consistent with the results of some previous studies (11,13,41).…”
Section: Discussionsupporting
confidence: 83%
“…As mentioned earlier, perceived barriers is a one of the HBM model constructs that has predictive power for health behaviors, and in this study it is used for determining the effective factors in the prostate cancer screening behaviors. These results are also consistent with the findings of Oliver et al (41). Participants in the study mentioned a lack of knowledge of where to go and how to do screening tests, a lack of emphasis on the screening tests, and a fear of thinking about the disease as the most common barriers to the prostate cancer screening.…”
Section: Discussionsupporting
confidence: 82%
“…An individual’s perceptions and psychosocial factors are also important factors for HBV screening behavior [12,13,14]. Where and how people acquire risk perception and knowledge about preventive health behavior is an important research question [15,16,17,18,19,20]. Very few studies have focused on how different sources of health information influence not only health knowledge, but also important psychosocial factors related to health behavior [21].…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies have focused on how different sources of health information influence not only health knowledge, but also important psychosocial factors related to health behavior [21]. Moreover, we have very limited understanding about how these acquired knowledge and perceptions relate to preventive behaviors [20]. To fill in this gap, we examined what the common information sources of HBV are and the associations with HBV screening behavior with a Health Belief Model (HBM) framework.…”
Section: Introductionmentioning
confidence: 99%
“…One interesting qualitative study looked at the barriers to and sources of influence for prostate cancer screening among rural men. The study found that most men in the study feared that prostate screening would be too embarrassing, painful, and long (Oliver et al 2011). …”
Section: Barriers To Screening and Preventionmentioning
confidence: 99%